Influence Roa, Structure AssetsGrowth Opportunity, Sales Growth And Current Ratio Towards Structure Capital Study Empirical In the Company Manufacturing Sector Industry On the Exchange Effect English 2013-2016 - Sri Arini, Lusia; Hutami Tri Adiningsih, Siti (Riviera Publishing, 2022)
Research in this study aims to determine the effect of return on assets, asset structure, growth opportunity, sales growth and current ratio of corporate capital structure simultaneously and partially. Capital structure is the ratio of total debt to own capital measured using the debt equity ratio (DER). With the object of research of manufacturing industry sector which experienced an increase that is food, beverage, cigarette, pharmacy, cosmetics, household and chemical goods listed in IDX period 2013-2016. This study was conducted as many as 44 population and 21 samples during the four-year period with a total of 84 samples using purposive sample method. The type of data used is secondary data sourced from Indonesia stock exchange and analyzed using multiple linear regression analysis. The results of this study show that simultaneously independent variables influence the dependent variable of the capital structure, but the growth of the asset structure and current ratio affect the capital structure with the conclusion the five independent variables contained 21% influence on capital structure.